A Rare Presentation of Acute Epididymoorchitis Leading to Infarction of Testes with Catastrophic Outcomes: Case Report and Literature Review - Harbhupinder Singh Sandhu; Harjinder Singh; Gurlivleen Kaur; Tejinder Kaur Kle; Sukhwinder Singh (GMC Patiala Journal of Research and Medical Education, 2021)
An acute scrotum is an emergency clinical scenario in urological emergency department. High resonance scrotal Sonography with colour Doppler is the imaging modality of choice for evaluation of acute scrotum as it helps in distinguishing between testicular torsion and epididymoorchitis, the two most important entities of testicular pain. Testicular infarction is a rare but potential devastating complication of epididymoorchitis. We report a rare case of epididymoorchitis evolving into testicular infarction and subsequently abscess leading to catastrophic outcomes inspite of receiving extended spectrum penicillins.